Exploring key blast and bacterial blight resistance genes in genetically diverse rice accessions through molecular and phenotypic evaluation - Prahalada, G.D.; Ramkumar, G.; Hechanova, Sherry Lou; Vinarao, Ricky; Jena, Kshirod K. (Wiley, 2017)
Blast and bacterial blight (BB) are the most dangerous rice (Oryza sativaL.) diseases that limit rice production significantly.Pib,Piz‐t, andPi9are reported as key resistance genes for blast whereasXa21,Xa4,Xa7, andxa13are considered as important resistance genes for BB. Using gene‐specific DNA markers, the presence of these resistance genes was screened in 211 diverse rice accessions originating from 26 countries. In molecular marker analyses, specific amplification patterns for thePibandPiz‐tresistance alleles were observed in 56 and 23 accessions, respectively, whereas thePi9resistance allele was not observed at all in these accessions. For BB, at least one BB resistance gene was present in 148 of the 211 evaluated accessions. All 211 accessions were evaluated for blast resistance using natural isolates and for BB resistance using Race 4 (PX071) and Race 6 (PX099). Among 211 accessions, 89 exhibited hypersensitive blast resistance reactions, whereas 85 and 37 accessions were rated as resistant or moderately resistance to BB Races 4 and 6, respectively. The combined analysis of molecular and phenotypic reactions (marker‐trait association assay) revealed that landraces possessed rare and several desirable genes compared with breeding lines with a narrow genetic base, hence these landraces serve as the valuable source for exploring new resistance genes for crop improvement. An interesting similarity in gene distribution pattern was observed inPibwithXa21and inPiz‐twithXa7. The analyzed blast and BB resistance genes were in a range of combinations in different landraces and breeding lines, which can be used in gene introgression and pyramiding programs as alternative resistance sources.